Chronic Follicular Conjunctivitis Secondary to Chlamydial Trachomatis - Nur Hafeela Mohamad Rusli; Safinaz Mohd Khialdin; Jemaima Che Hamzah (Pusat Perubatan Universiti Kebangsaan Malaysia, 2022)
Chronic follicular conjunctivitis is commonly caused by Chlamydia trachomatis infection. Patients usually present with non-resolving conjunctivitis which is associated with tender lymphadenopathy. We report a case of a monogamous young female with chronic inclusion conjunctivitis. A 34-year-old healthy female presented with redness of the left eye (LE) for 3 days, associated with blurred vision and ocular discharge. Visual acuity (VA) of the right eye (RE) was 6/6 and 6/24 in LE with pinhole 6/6. There was mucopurulent discharge over the LE with injected conjunctiva and follicular reaction involving the upper eyelid. She was treated as LE bacterial conjunctivitis and started on topical eyedrops ciprofloxacin 0.3% and artificial tear eye drops every 2 hours. She denied any history of contact with patients with similar history or history of sexually transmitted infection. She discontinued treatment and presented again 3 weeks later with bilateral eyes injected with follicular reactions and the presence of a thin pseudomembrane over the upper eyelids associated with painful preauricular lymph nodes. Noted generalized punctate epithelial erosions (PEE) over bilateral eyes with mucous strands adhered to cornea epithelium. A corneal epithelial defect of 3.7 mm(V) x 4 mm(H) was noted in the RE. The VA in the RE was 6/18 with pinhole 6/12, and 6/9 in the LE, with pinhole the same. The diagnosis of bilateral follicular conjunctivitis with filamentous keratoconjunctivitis secondary to Chlamydia trachomatis was confirmed by a positive conjunctival smear. She was then treated with fucithalmic ointment twice daily and tetracycline 250 mg orally four times daily for three weeks. Signs and symptoms disappeared after completion of tetracycline treatment.